Estimation of TSH, T3, T4 and Testosterone Concentrations in Patients Suffering From Myocardial Infarction (MI) in Baghdad City-Iraq - Noori Mohammed Luaibi (Journal of Global Pharma Technology, 2017)
The most common cause of morbidity and mortality is cardiac disease, even minor alterations in thyroid hormone levels adversely effects on the cardiovascular system. In acute cardiac problems hypothyroidism occurs and it is associated with the increase of cardiac mortality. The purpose for this study is to investigate the alterations in hormone concentrations TSH , T3 , T4 , and testosterone  in patients suffering from myocardial infarction  in Baghdad city According to statistical analysis  revealed that the level of T3 , T4 and testosterone  were decreased in comparison with healthy control group and the decreasing value of these hormones were continuing to occur especially in 7 and 14 days after myocardial infarction occurs .While the levels of TSH illustrated increment in various periods of time used in this study after admission of myocardial infarction.Keywords: Myocardial infarction, TSH, T3, T4, Testosterone.